(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objectives: To compare the efficacy of letrozole versus clomiphene citrate in ovulation induction and pregnancy rate in patients with polycystic ovarian disease. Design:Randomized controlled trial. Place and duration of study: Moula Bakhsh Teaching Hospital And Diagnostic Centre Sargodha from January 2013 to June 2013. Subject and Method: 200 patients with polycystic ovarian disease selected by non probability purposive sampling were included. Efficacy was determined in terms of ovulation induction when follicular size of more than or equal to 17mm is achieved on transvaginal ultrasound and pregnancy rate is checked by urine for pregnancy test in those patients with successful ovulation induction in the same cycle. Result: 63.6% patients had successful ovulation induction with letrozole and 29.4% patients having clomiphene citrate showed successful ovulation induction .The pregnancy rate in letrozole group was 23.6% and in clomphene citrate group it was 9.3%. Conclusion: Letrozole is superior to clomiphene citrate in achieving successful ovulation induction and subsequent pregnancy rate in patients with polycystic ovarian disease.